The Postmaster - Lincoln, Joseph Crosby, 1870-1944; Heath, Howard, 1879- (Salt Lake City, UT : Project Gutenberg, 2011)
"The Postmaster" by Joseph C. Lincoln is a novel written in the early 20th century. The story begins with Zebulon Snow, a retired sea captain who decides to leave his seafaring life behind to settle down in Ostable, the town of his birth. As he aims to enjoy a life of leisure, he soon finds himself unexpectedly drawn into the challenges and responsibilities of running a small country store alongside his quirky partner Winthrop Adams Beanblossom. At the start of the narrative, the protagonist grapples with the contrast between his hopes for a peaceful retirement and the monotony that ensues after leaving his sea captain duties. As he embarks on this new chapter of life, he becomes involved in bets and conversations about work and marriage, revealing his struggles with change and his reluctance to engage in any responsibilities. Zebulon's humorous reflections on his life, combined with a vivid portrayal of small-town life and a cast of colorful characters$1 (Bmost notably the anxious Beanblossom$1 (Bset the stage for a lighthearted exploration of community dynamics and personal growth. The opening encapsulates both the comedic elements and the deeper themes of identity and purpose that are likely to unfold throughout the novel. (This is an automatically generated summary.)s
Release date is 2011-09-19
Roger Frank, Mary Meehan, and the Online Distributed Proofreading Team at http://www.pgdp.net.
Keywords: Love stories; New England -- Social life and customs -- Fiction; Middle-aged men -- Fiction; Cape Cod (Mass.) -- Fiction; Business -- Fiction